Better together: Subgenomes for allotetraploid potato wild relative Solanum acaule Bitt. reveal origins in Petota Clade 3 and 4 - Achakkagari, S.; Camargo‐Tavares, J.C.; Praslickova, D.; Martini, C.; Bizimungu, B.; Anglin, Noelle L.; Manrique, N.; Lindqvist-Kreuze, H.; Tai, H.H.; Stromvik, M.V. (2025)
Potato wild relatives (Solanum section Petota) are a source of genetic diversity for climate-smart improvement of modern cultivars (Solanum tuberosum). The allotetraploid Solanum acaule Bitter. has been previously used to introgress frost tolerance into potato cultivars such as Yukon Gold and Viking. The current study presents the subgenomes of S. acaule. In a phylogenetic context, the placement of the individual subgenomes shows that Solanum megistacrolobum (Clade 4) is the progenitor species of S. acaule subgenome 2, while the progenitor species of subgenome 1 (mapping to Clade 3) is still unknown and may be extinct. The genome assembly is 1.34 Gb in 24 chromosomes with an N50 of 56.2 Mb, making the theoretical tetraploid S. acaule genome 2.68 Gb. The C-repeat binding factor (CBF) cold response genes were identified in the subgenomes, and in a freeze-challenged transcriptome analysis of S. acaule compared with autotetraploid S. tuberosum 'Atlantic', CBF1 was induced in both species, while CBF4 (subgenome 2) was induced only in S. acaule. A general subgenome expression bias was not detected in a set of homoeologous genes, though the subgenomes diverged in the number of differentially expressed genes and their functional roles.